2021
DOI: 10.1155/2021/6706345
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synergetic LSTM-GA Stock Trading Suggestion System in Internet of Things

Abstract: The Internet of Things (IoT) play an important role in the financial sector in recent decades since several stock prediction models can be performed accurately according to IoT-based services. In real-time applications, the accuracy of the stock price fluctuation forecast is very important to investors, and it helps investors better manage their funds when formulating trading strategies. It has always been a goal and difficult problem for financial researchers to use predictive tools to obtain predicted values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In 2021, Wu and Ming-Tai proposed the SACLSTM stock price prediction algorithm, which constructs a sequence array of historical data and its leading indicators and uses the array as the input image of the CNN framework, and this algorithm has achieved excellent forecasting results for Taiwan and American stocks [22], which is similar to the work proposed by the authors in reference [23]. An LSTM-GA stock trading suggestion system in IOT was proposed, based on historical data and leading indicators [24]. In 2022, Zhang et al…”
Section: Related Workmentioning
confidence: 56%
“…In 2021, Wu and Ming-Tai proposed the SACLSTM stock price prediction algorithm, which constructs a sequence array of historical data and its leading indicators and uses the array as the input image of the CNN framework, and this algorithm has achieved excellent forecasting results for Taiwan and American stocks [22], which is similar to the work proposed by the authors in reference [23]. An LSTM-GA stock trading suggestion system in IOT was proposed, based on historical data and leading indicators [24]. In 2022, Zhang et al…”
Section: Related Workmentioning
confidence: 56%
“…It is reported that Elman with direct input–output connection helps in improving accuracy, while reducing network complexity and computational cost. Recent work by researchers (Wu et al 2021b ) proposed a trading suggestion system based on Synergetic LSTM-GA. Their experimental outcomes over five Taiwan stocks revealed that LSTMLI-GA framework was able to achieve a higher profit margin as compared to other models. Day-ahead stock price prediction framework by authors (Wu et al 2021a ) combined CNN and LSTM to form a hybrid predictor framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One deep learning technique that can be used for time series is the Recurrent Neural Network (RNN), which is designed to work with sequential data [10] [11]. The progress of RNN is growing quite rapidly in various fields, but RNN has a weakness in processing time series because, [12] performance for prediction will have a negative effect if the sequence size is relevantly long and the other is that the RNN gradient will be lost, resulting in longterm memory failure. Unlike the RNN, LSTM can manage memory for each input by using memory cells and gate units [13].…”
Section: Introductionmentioning
confidence: 99%